2018
DOI: 10.5539/ijef.v10n6p160
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Stock and Treasury Bills under Inflation and Floating: Evidence from Egypt

Abstract: The aim of this study is comparing the performance of common stock & treasury bills, according to the central bank of Egypt and their monetary policy during the time period between “1994-2017”, using descriptive & inferential statistical methods. The Study concluded that there is a strong positive relationship between inflation rate & returns of Egyptian treasury bills, as the same relation as with floating Egyptian pound.in addition, the study found the impact of Inflation and Floating on the retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…According to Titman et al (2021), purchasing luxurious corporate jets and firm apartments and paying for resort hotels during vacations are examples of this spending. Although utilizing different logical explanations, this evidence of the positive relationship between debt policy and market risk is supported by Saji (2018), Arora et al (2019), Wagdi and Tarek (2019), Jaafar et al (2020), Saravia et al (2021) and Mousa et al (2021).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…According to Titman et al (2021), purchasing luxurious corporate jets and firm apartments and paying for resort hotels during vacations are examples of this spending. Although utilizing different logical explanations, this evidence of the positive relationship between debt policy and market risk is supported by Saji (2018), Arora et al (2019), Wagdi and Tarek (2019), Jaafar et al (2020), Saravia et al (2021) and Mousa et al (2021).…”
Section: Discussionmentioning
confidence: 94%
“…Saji (2018), Mousa et al (2021), andSaravia et al (2021) display a positive effect using a single regression model. Moreover, Wagdi and Tarek (2019) prove a positive impact when the debt-to-equity ratio is used; unfortunately, they verify the opposite sign when utilizing the long-term debt-to-equity ratio as the proxy. With the polling data regression model, Arora et al (2019) exhibit that financial leverage is positively associated with this systematic risk but meaningless evidence when the fixed effect model is employed.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…As this study and others indicated that there is a positive correlation between risk and return. (Elbannan, 2015;Wagdi and Tarek, 2019), which is one of the pillars of traditional monetary theory. Previous research has shown a favorable link between CEO narcissism and takeovers in certain areas, such as mergers and acquisitions (M&A).…”
Section: Introductionmentioning
confidence: 99%